THE ROLE OF DATA IN THE NEEDS ANALYSIS PROCESS: LITERATURE REVIEW OF PRACTICES AND CHALLENGES IN EDUCATIONAL INSTITUTIONS - Saputri, Endang; Hidayat, Rahmad; Darimis, Darimis; Dasril, Dasril; Putra, Yendri; Sakti, Zulabna Widya (World Psychology, 2026)
Needs analysis is a crucial step in planning and improving educational services. Data utilization is a key aspect in ensuring that the needs analysis process is conducted objectively and on target. This article aims to examine the role of data in the needs analysis process, focusing on implementation practices and challenges faced by educational institutions. The research method used is a literature review, examining various relevant scientific publications related to the implementation of data-based needs analysis. The review results indicate that data plays a strategic role in identifying service gaps, establishing program priorities, and supporting evidence-based decision-making. However, the implementation of data-based needs analysis still faces various obstacles, such as limited competency of educators in data management, suboptimal data accuracy and availability, minimal technological support, and an underdeveloped data utilization culture. This article emphasizes the need to strengthen human resource capacity, improve information system infrastructure, and develop a culture of data literacy in educational institutions to ensure effective data utilization in needs analysis. The findings of this study are expected to serve as a reference in policy development efforts and improve the quality of educational services.